Demographic and Clinical Profiles of Burn Fatalities in Bangladesh: A Morgue Based Study of 405 Autopsies (Journal of Brahmanbaria Medical College, 2026)
Introduction: Deaths due to burn are an important public health related issue in a developing country like Bangladesh.Burn injuries have been described as the most serious injuries that may afflict a human being. It is a considerable one of the commonest cause of unnatural deaths in Bangladesh. Females, child, rural dwellers and populations of low socioeconomic condition are mostly suffered by burn injuries. The purpose of this retrospective study was to record and evaluate the actual and potential causes and the magnitude of the fatal burn injuries.Materials and methods: This retrospective cross-sectional study was conducted among the burn death victims at Dhaka Medical College, Morgue, during the period of January 2023-December 2023.Results: An analysis of autopsy records revealed 405 (11.27%) cases of burn injuries among the total 3589 autopsies done over 1 year period (January 2023-December 2023) in the mortuary of Dhaka Medical College. Among the total burn cases the flame burns were seen in 76.79% of the victims, out of these fire was the commonest cause (71.71%). The majority of deaths (21.89%) occurred between 31 and 40 years of age group with a preponderance of males (66.73%) female maleratio being 1:2. Most of the victims died from neurogenic shock (54.73%) followed by septicemia (23.59%). The majority of deaths occurred within a week (80.82%) and the percentages of burns (TBSA) over 50% were observed in most of the cases (83.27%). Accidental death was the most common manner of burn death accounting for 331 (81.65%)and the commonest location for burn deaths was home locations 259 (63.89%). Highest incidence of burn occurred in winter 170 (42.03%) regarding variations in burn injury with time of day, the incidence is high in night 219 (54.07%) day night ratio being 1:1.18. Conclusion: The results of this study provide the necessary information’s to address it as a public health related problem and develop proper burn prevention programs, thus reducing the frequency of burns and burn related deaths.Journal of Brahmanbaria Med. Coll. Volume 07 Issue 01 Jan 2025 ; 3-7